Interrelation of acting techniques and scenic speech. (Eurasian Journal of Philology Science and Education, 2015)
Relevance of research – when reviewing History of Art of any country, one may observe a distinctive pattern in imperative demands of time in the making and intensive development of Arts. One of the integral parts of such pattern, elocution, currently constitutes a significant social cause. This phenomenon occurs in the manner of speech of artists, including stage and film actors and directors, television and radio hosts andmasters of artistic speech, vocal singers, as well as ecclesiastic superiors in mosques and preachers, lecturers and educators, lawyers and judges, public figures and leaders of organizations, in broader terms, professionalsrelated to the art of speech, which contradicts the characteristic aspects of speech. Thus, the rationale of the study is advanced by current conditions, which require constant practice of oral culture accumulated in the speech culture of actors over the years and perfection of scenic speech as consistent with modern theatrical art. As the scope of speech culture is broad and functions carried out by the speech culture are rather versatile, this scientific work is fundamental and requires consistent study of significance and specific characteristics of scenic speech and presentation of an elaborated program for future actors, other specialists associated with oral culture and a community of individuals who wish to master oratorical skills.
Keywords: аctor; acting; speech; stage speech; verbal action; theater; pedagogy; сulture of Speech